Characterization of CoNi based catalyst for water gas shift reaction - Halim, Noor Azlina; Nasri, Noor Shawal; Songip, Ahmad Rahman (2005)
In order to avoid the proton exchange membrane fuel cell (PEMFC) anode (Pt) to be poisonous, the amount of carbon monoxide (CO) in hydrogen stream must be less than 10 ppm. So, water gas shift reaction (WGSR) is applied to purify the hydrogen stream before entering the PEMFC. An emerging use for WGS reaction is on-board hydrogen production for fuel cell vehicles. In WGSR, catalyst plays an important role. The WGSR system in this study used CoNi based (ATR catalyst) as its catalyst. To improve the performance of the catalyst, three different promoters were added to each different sample. They are manganese (Mn), iron (Fe) or chromium (Cr). The main objective of this paper is to study the characterization of X-CoNi/MgO (X= Mn or Fe or Cr) for WGSR. Firstly, each catalyst had to undergo the X-ray Diffraction (XRD) analysis. This analysis is conducted to identify the crystalline phases that were present. Furthermore, Temperature Programmed Reduction (TPR) was used to observe the concentration of reducible species present in the catalyst. From XRD and TPR, all of catalysts were found to be free from NiO and CoO that contribute to sintering and coke formation. TPR also represents the activity of catalysts were related with reduction temperature. The activity of catalysts was increased when temperature reduction of catalyst was increased. From the results of experiment, FeO-NiOCoO/MGO with 3wt% has a high activity compared to others.